The Danish labor market, 2000-2016 - Torben M. Andersen (IZA World of Labor, 2017)
Denmark is often highlighted as a “flexicurity” country characterized by rather lax employment protection legislation, generous unemployment insurance, and active labor market policies. Despite a sharp and prolonged decline in employment in the wake of the Great Recession, high job turnover and wage adjustments worked to prevent long-term and thus structural unemployment from increasing. While many have been affected by unemployment, most unemployment spells have been short, which has muted the effects on long-term and youth unemployment. Recent years have seen a sequence of reforms to boost labor supply and employment, including measures targeting the young, the elderly, and immigrants.
Keywords: 330; flexicurity; business cycles; structural policies; youth unemployment; immigration